1987
DOI: 10.1111/j.1476-5381.1987.tb11381.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory neuropeptide effects in human skin

Abstract: 1Neuropeptides released from sensory nerves may account for cutaneous flare and wheal following local trauma. In 28 normal subjects we have studied the effects of four sensory neuropeptides given by intradermal injection on the forearm or back. 2 All peptides caused a flare distant from the site of injection, presumably due to an axon reflex. Substance P (SP) was the most potent (geometric mean dose causing 50% ofmaximum flare, 4.2 pmol). Neurokinin A (NKA) was the next most potent with neurokinin B (NKB) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
1

Year Published

1988
1988
2005
2005

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 31 publications
7
63
1
Order By: Relevance
“…The hypothesis, however, is not consistent with the lack of potentiation in human skin, in which SP is active (Fuller et al, 1987). The potentiation in rat skin has been suggested as being due to vasodilatation (Gamse & Saria, 1985).…”
Section: Drugs and Chemicalscontrasting
confidence: 40%
See 1 more Smart Citation
“…The hypothesis, however, is not consistent with the lack of potentiation in human skin, in which SP is active (Fuller et al, 1987). The potentiation in rat skin has been suggested as being due to vasodilatation (Gamse & Saria, 1985).…”
Section: Drugs and Chemicalscontrasting
confidence: 40%
“…Previous studies have demonstrated species differences in regard to potentiation by CGRP of SP-induced microvascular leakage when both are injected intradermally. In rabbit and man (Fuller et al, 1987), CGRP does not potentiate SP-induced wheal. In contrast, there is potentiation in rat skin Gamse & Saria, 1985).…”
Section: Drugs and Chemicalsmentioning
confidence: 99%
“…Both neurokinin A (substance K) and neurokinin B (neuromedin K) were extracted from mammalian spinal cord (Kimura et al, 1983;Kangawa et al, 1983;Minamino et al, 1984). Like substance P, neurokinin A and neurokinin B increase microvascular permeability causing local oedema formation when injected into rat skin (Gamse & Saria, 1985) and human skin (Devillier et al, 1986;Fuller et al, 1987). The tachykinins do not possess a common N-terminus (see Table 1) and the neurokinins are >50 times less potent than substance P in stimulating histamine release from rat peritoneal mast cells (Devillier et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The inflammation is inhibited by pretreatment with capsaicin [4,5], which depletes sensory neurons of SP [7], and by SP antagonists [8]. SP and neuro kinin A also increase the vascular permeability in the skin when administered intradermally [9][10][11][12][13]. In addi tion, it has been shown that the reactivity to a variety of stimuli is increased in various tissues and cells of asthmatics [14][15][16][17], Therefore, for better understand ing of the pathophysiology of asthma, it seems to be important to know whether the reactivity to tachykin ins is altered in asthmatics in comparison with that of normal subjects.…”
Section: Introductionmentioning
confidence: 99%